Predictors of organizational citizenship behavior among government personnel: A structural equation modeling approach - Nitafan, Rowell P.; Idris, Fatma M. (Faculty of Social and Political Science, Universitas Airlangga, 2024)
The study aimed to develop a causal paradigm of organizational citizenship behavior among government personnel in the SOCCSKSARGEN Region. 400 employees were selected through stratified balanced sampling. Data were collected using survey questionnaires and analyzed through the mean, Pearson r, multiple regression, and structural equation modeling. The study determined that quality of work life, employee silence, and political skill statistically correlate with organizational citizenship behavior. The study inferred the predictive capacity of the exogenous latent variables in influencing the organizational citizenship behavior of LGU employees. There were five generated models of organizational citizenship behavior, and model five was determined as the best-fit structural model. The model retained five quality indicators of work life, namely compensation and rewards, training and development, relationships and cooperation, organizational culture and climate, and work environment. Prosocial silence and acquiescent silence remained as indicators of employee silence. Political skill was narrowed to three indicators, comprising social astuteness, interpersonal influence, and networking ability. Finally, altruism and civic virtue emerged as the strongest indicators of organizational citizenship behavior.